2016
DOI: 10.1097/qad.0000000000001223
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T cells with an activated and exhausted phenotype distinguish immunodeficiency during aviremic HIV-2 infection

Abstract: Objective:HIV type 2 (HIV-2) represents an attenuated form of HIV, in which many infected individuals remain ‘aviremic’ without antiretroviral therapy. However, aviremic HIV-2 disease progression exists, and in the current study, we therefore aimed to examine if specific pathological characteristics of CD4+ T cells are linked to such outcome.Design:HIV-seronegative (n = 25), HIV type 1 (HIV-1) (n = 33), HIV-2 (n = 39, of whom 26 were aviremic), and HIV-1/2 dually (HIV-D) (n = 13)-infected study participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 44 publications
6
33
0
Order By: Relevance
“…Despite CD4+ T cells are critical for control of viral infections, less is known about their co-expression pattern of inhibitory receptor in HIV-1 infection and in relation to healthy subjects. Our preliminary studies showed negligible expression of Tim-3, LAG-3, and CD160 on CD4+ T cells and a strong association of 2B4 and KLRG-1 with effector CD4+ T cells (data not shown), similar to as described in other studies ( 15 , 21 , 29 , 30 ). We therefore focused on assessing the expression pattern of PD-1, CTLA-4, and TIGIT on different CD4+ memory T cell populations, defined by surface markers CD27, CD45RO, and CCR7, using multiparametric flow cytometry.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Despite CD4+ T cells are critical for control of viral infections, less is known about their co-expression pattern of inhibitory receptor in HIV-1 infection and in relation to healthy subjects. Our preliminary studies showed negligible expression of Tim-3, LAG-3, and CD160 on CD4+ T cells and a strong association of 2B4 and KLRG-1 with effector CD4+ T cells (data not shown), similar to as described in other studies ( 15 , 21 , 29 , 30 ). We therefore focused on assessing the expression pattern of PD-1, CTLA-4, and TIGIT on different CD4+ memory T cell populations, defined by surface markers CD27, CD45RO, and CCR7, using multiparametric flow cytometry.…”
Section: Resultssupporting
confidence: 90%
“…Recent studies in mice have demonstrated a relationship between the transcription factors FoxP3 and Ikzf2 (Helios), and an exhausted state for CD4+ T cells in chronic LCMV infection ( 20 ), findings that could be of translational importance in HIV-1 disease. In the setting of HIV-1, studies have shown that HIV-infected subjects harbor increased levels of CD4+ T cells expressing PD-1, Lag-3, CTLA-4, and 2B4, among others ( 11 , 12 , 21 23 ). Furthermore, several studies on ELCs have shown that natural control of HIV-1 is associated with more vigorous and polyfunctional responses of HIV-specific CD4+ T cells ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acute HIV infection is associated with high levels of CD4 + and CD8 + T cell activation and exhaustion, which is often maintained throughout chronic infection due to prolonged exposure to antigenic and inflammatory signals even in anti-retroviral-treated individuals ( 74 , 75 ). Markers of T cell activation, such as CD38 and HLADR, remain elevated above normal in HIV positive individuals with durable viral suppression on ART ( 76 ). Moreover, elevated expression of co-inhibitory receptors, such as PD-1, TIGIT, CD160, and 2B4, is associated with functionally exhausted HIV-specific and non-specific CD8 + T cells with reduced proliferative capacity and impaired effector functions ( 77 80 ).…”
Section: Immune Activation and Exhaustion Are Key Hallmarks Of Hiv Inmentioning
confidence: 99%
“…This subpopulation of T cells enters an "exhausted" state, characterized by low cytokine production, low proliferation, and expression of a series of inhibitory receptors. The most well studied of these receptors include PD-1, CTLA-4, and LAG-3, which interact with a range of ligands to activate negative regulatory pathways (13,14). While these inhibitory receptors may balance an overly activated immune response that could lead to disease pathology, the receptors can also prevent an effective immune response from clearing infections and tumor cells.…”
mentioning
confidence: 99%
“…Confounding these data, the relationship between inhibitory markers and functional exhaustion is not abundantly clear. Recent studies have shown that inhibitory receptors can act as activation markers and that T cells can simultaneously express both inhibitory and activation markers (14,(32)(33)(34)(35). Therefore, it becomes difficult to distinguish T cell exhaustion using inhibitory receptors alone.…”
mentioning
confidence: 99%